Modelo de investigación en la sociología del derecho (Società e diritti, 2022)
The research method of the Sociology of Law is described: problem, hypothesis, analysis of the hypothesis with the data and the results that account for the knowledge obtained about the investigated problem. A novel classification of problems and hypotheses is presented. The role played by the variable and its typology are discussed. The data and its collection techniques. The statistically significant sample and selection by using a table of random numbers. With a concrete example, the analysis of the hypothesis is executed with the data. The results of the investigation are examined considering the fate of the hypothesis in relation to the problem, the interpretation of these and the probable explanation.